AN OVERVIEW OF THE LEGAL FRAMEWORK OF THE BANKING UNION - Podgórski, Maciej (Review of European and Comparative Law, 2018)
The article provides an overview of the legal structure of the Banking Union consisting of two pillars – the Single Supervisory Mechanism and the Single Resolution Mechanism. As a point of departure, it discusses the reasons for the creation of the Banking Union. Then, it analyses the legal structure of the Single Supervisory Mechanism in order to compare it to the legal framework of the Single Resolution Mechanism and shows that the differences in their design are a corollary of disparate legal bases for both instruments. Finally, it argues that the disputed legal basis for the regulation establishing the Single Resolution Mechanism is sufficient in light of Meroni doctrine as formulated in the Short-selling case.